Belief control systems, psychological empowerment, and service motivation: A path to organizational effectiveness - Nazaruddin, Ietje; Hasna, Afifah (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2023)
This study examines how belief control systems affect public service motivation, focusing on the role of psychological empowerment. Using purposive sampling techniques, we selected a sample of 150 permanent public servants from the local bureaucracy in Yogyakarta, Indonesia. Data analysis was conducted using SEM-PLS analysis with Smart-PLS 4.0 software. Our findings indicate that belief control systems do not directly impact individuals' motivation to deliver efficient public services. However, psychological empowerment mediated the relationship between belief control systems and public service motivation. These results contribute to the existing literature by providing empirical evidence of the influence of belief control systems on public service motivation through psychological empowerment. The study underscores the importance of fostering positive belief control systems and enhancing psychological empowerment to improve performance and service delivery in the public sector. Understanding these dynamics is crucial for policymakers and practitioners to incentivize employees effectively and enhance public service outcomes.